Social Knowing, Mental Health, and the Importance of Indigenous Resources: A Case Study of Indigenous Employment Engagement in Southwestern Ontario - Jewell, Eva; Doucet, Andrea; Falk, Jessica; Fyke, Susan (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2020)
This article addresses employment/unemployment engagement experiences of Indigenous peoples living in a region of present-day southwestern Ontario, as well as the wider socio-economic, cultural, and historical contexts of those experiences. The qualitative research study that informs this paper was conducted with and at the request of an Indigenous organization in southwestern Ontario with the aim of broadening understandings of the multiple factors that lead to disadvantages amongst Indigenous peoples living in a settler-colonial neoliberal society. Based on focus groups/sharing circles with 21 Indigenous youth and adults and interviews with local employers in southwestern Ontario, our study reveals that when Indigenous peoples have access to cultural knowing, critical Indigenous education opportunities, and strong support networks, they are better able to access and advocate for employment opportunities and their well-being. Yet, they face challenges in navigating these resources and spaces due to what Kristie Dotson (2014) refers to as ‘epistemic oppression’, issues related to poverty, mental health, and intergenerational trauma, all of which are intricately connected to settler colonialism and Canadian Federal Indian Policy. Overall, Indigenous organizations provide urban communities with pathways to, and respite from, neoliberal societal expectations. Résumé Cet article traite des expériences des peuples autochtones vivant dans une région du sud-ouest de l’Ontario quant à l’emploi et au chômage, et plus généralement, des contextes socio-économique, culturel et historique liés à ces expériences. La recherche quantitative sur laquelle est fondé cet article a été menée avec l’aide d’une organisation autochtone du sud-ouest de l’Ontario, par leur requête, afin d’approfondir notre compréhension des multiples facteurs qui défavorisent les peuples autochtones vivant dans une société de colonialisme de peuplement néo-libérale. À travers des groupes de discussion et des cercles de partage avec 21 Autochtones, jeunes et adultes, ainsi que des entrevues avec des employeurs locaux du sud-ouest de l’Ontario, notre étude démontre que les peuples autochtones sont plus en mesure d’améliorer leurs opportunités de travail et leur bien-être, ainsi que les défendre, lorsqu’ils ont accès au savoir culturel, à des possibilités d’éducation autochtones essentielles et à un réseau de soutien solide. Pourtant, ils peinent à utiliser ces ressources et les espaces en raison de ce que Kristie Dotson (2014) appelle « l’oppression épistémique », soit des problèmes se raccordant à la pauvreté, à la santé mentale et au traumatisme intergénérationnel, ces derniers étant étroitement liés au colonialisme de peuplement et à la politique indienne du gouvernement fédéral du Canada. Globalement, les organisations autochtones offrent aux communautés urbaines des débouchés ainsi qu’un répit face aux attentes de la société néo-libérale. Mots clés: Autochtones; savoir culturel; déterminants de la santé des peuples autochtones; emploi; éducation